2021
DOI: 10.1111/ijac.13905
|View full text |Cite
|
Sign up to set email alerts
|

Study on cobweb‐like carbon nanotubes/calcium aluminate cement and its effect on the properties of Al2O3–SiC–C castables

Abstract: Cobweb‐like carbon nanotubes/calcium aluminate cement (CNTs/CAC) were synthesized through catalytic sintering with citric acid, calcium carbonate, and alumina as raw materials and ferric chloride as catalyst precursor. The products were characterized by X‐ray diffractometry, scanning electron microscopy, Raman spectroscopy, and high‐resolution transmission electron microscopy. The in situ cobweb‐like carbon firmly bonded between calcium aluminate grains, which endows the better oxidation resistance and water d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Nevertheless,the high temperature oxidation of carbon (C) reduces the service life of ASC castables and limits their application [4][5][6]. As a result, to solve the issues, various methods and techniques have been developed, including changing the morphology of the introduced C such as graphitic carbon sphere [7],cobweblike carbon nanotubes [8] and modified coal tar pitch [9],adding antioxidants such as andalusite [10,11], Si2BC3N [12]and Al [13], and formation in-situ whiskers reinforcement [14][15][16].Among them, the most popular is adding metal and its alloy powders to ASC castables, which can not only improve its oxidation resistance, but also improve its toughness due to the reinforcing phases that were formed in-situ in ASC castables. For example, Sun et al [17] found that the addition of 4 wt.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless,the high temperature oxidation of carbon (C) reduces the service life of ASC castables and limits their application [4][5][6]. As a result, to solve the issues, various methods and techniques have been developed, including changing the morphology of the introduced C such as graphitic carbon sphere [7],cobweblike carbon nanotubes [8] and modified coal tar pitch [9],adding antioxidants such as andalusite [10,11], Si2BC3N [12]and Al [13], and formation in-situ whiskers reinforcement [14][15][16].Among them, the most popular is adding metal and its alloy powders to ASC castables, which can not only improve its oxidation resistance, but also improve its toughness due to the reinforcing phases that were formed in-situ in ASC castables. For example, Sun et al [17] found that the addition of 4 wt.…”
Section: Introductionmentioning
confidence: 99%